PENEGAKAN HUKUM TINDAK PIDANA PERDAGANGAN ORANG DI WILAYAH KEPOLISIAN DAERAH JAWA TIMUR - Andi Ines Audryana Bachtiar; Yana Indawati (Pusat Riset dan Inovasi Nasional, 2023)
Human trafficking is an organized crime that violates human rights relating to freedom, security and has the potential to use acts of violence against victims. This research uses empirical juridical research methods by examining a phenomenon that occurs in society associated with the applicable laws. The research was conducted to find out the law enforcement against the crime of trafficking in persons, the obstacles in the implementation of law enforcement, and how the police efforts as law enforcers who act to handle obstacles at the level of investigation and investigation. The results showed that law enforcement of trafficking in persons was dominated by trafficking in persons with sexual utilization and trafficking in Indonesian migrant workers. Case handling begins with a public report then submitted to the unit handling human trafficking cases for a series of investigations, investigations, and submission of files to the prosecutor's office. There are different methods in handling cases tailored to the needs of cases of trafficking in persons with sexual exploitation or exploitation and migrant workers. Based on the research, it is known that investigators find various obstacles caused by internal factors or the investigation process itself and external factors or from the community. Law enforcement is carried out with the aim of restoring the law itself so that evaluation is needed so that the handling of human trafficking crimes runs effectively.